Scherbius wind farm based fuzzy SSSC - Talebi Abderrahmane; Tedjini Hamza (Institute of Advanced Engineering and Science, 2020)
The wind is a clean, free, and readily available renewable energy source, it is cost-effective in several regions, it is a domestic source of energy and it is a sustainable source of energy. The SSSC system is a FACTS voltage compensator, it is inserted in series with the electrical transmission line through a coupling transformer, its role is to inject a voltage which allows to influence the active power transmitted. The goal of this paper is to examine the effect of using a wind farm SSSC to improve flexibility of a multi-machine perturbed network.